2014
DOI: 10.1113/jphysiol.2014.270850
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal hormones and the dialogue between gut and brain

Abstract: The landmark discovery by Bayliss and Starling in 1902 of the first hormone, secretin, emerged from earlier observations that a response (pancreatic secretion) following a stimulus (intestinal acidification) occurred after section of the relevant afferent nerve pathway. Nearly 80 years elapsed before it became clear that visceral afferent neurons could themselves also be targets for gut and other hormones. The action of gut hormones on vagal afferent neurons is now recognised to be an early step in controlling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
109
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(114 citation statements)
references
References 93 publications
2
109
0
3
Order By: Relevance
“…In our preliminary studies on the volume of intestinal serotonergic cells in experiment 2, we found an increase from middle to distal gradient in the volume density, and enteral nutrition with BC tended to increase the volume density of serotonergic cells distally, relative to IF and TPN. Correspondingly, the distal part of the intestine is also more sensitive to the trophic effects of enteral diet than the proximal region (see Table 2 for experiments 1 and 2), probably because of a larger number of enteroendocrine and immune cells mediating these effects (9). Our analyses of the diet-dependent secretion of serotonin also suggested that MEN-BC pigs had higher serotonin levels in platelet-free plasma, relative to TPN pigs, with intermediate values for MEN-IF pigs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our preliminary studies on the volume of intestinal serotonergic cells in experiment 2, we found an increase from middle to distal gradient in the volume density, and enteral nutrition with BC tended to increase the volume density of serotonergic cells distally, relative to IF and TPN. Correspondingly, the distal part of the intestine is also more sensitive to the trophic effects of enteral diet than the proximal region (see Table 2 for experiments 1 and 2), probably because of a larger number of enteroendocrine and immune cells mediating these effects (9). Our analyses of the diet-dependent secretion of serotonin also suggested that MEN-BC pigs had higher serotonin levels in platelet-free plasma, relative to TPN pigs, with intermediate values for MEN-IF pigs.…”
Section: Discussionmentioning
confidence: 99%
“…There is rapidly increasing evidence of functional links among the gastrointestinal tract (GIT), the diet, and the brain, especially in early life (9). Growth rate and nutrient intakes in early life may affect later neuromuscular and cognitive outcomes, but the mechanisms are largely unknown (10).…”
mentioning
confidence: 99%
“…Hence, this constant stimulation is a major stimulus to gastric emptying [17][18][19][20] along with many hormones, such as cholecystokinin; and neural pathways, such as parasympathetic stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…We could not measure the plasma CCK concentrations in the present study, because we did not get the permission from the Ethical Committer to draw the blood from the participant. However, the role of CCK in the inhibition of gastric emptying was suggested to be mediated via CCK-1Rs on the vagal afferent nerve terminals distributed on the stomach and upper small intestine (7,23). That is, CCK released from endocrine cells (I cells) in the upper small intestine could bind CCK-1Rs directly (via a paracrine pathway) without any increase in the plasma CCK level.…”
Section: Retention Times Of Vodka and Water In The Stomach During Thementioning
confidence: 99%